Functionality Validation of the New QOS and Security Integration Model for Manet - Papaj, Jan; Dobos, Lubomir; Cizmar, Anton (Communications - Scientific Letters of the University of Zilina, 2013)
In this article, the simulation testbed of the new designed model for cooperation between QoS and security is introduced. The field of research about QoS and security provide dynamically developed and important areas of the research and up to now no protocol or mechanisms have been designed to this process. The cooperation is based on using a Cross Layer Design model (CLD) and modified Security Service Vector (SSV). A main idea of testbed is the indication how could security and QoS be integrated as a parameter to the MANET via this model. We also show how this model can affect the functionalities of the whole MANET.
Keywords: MANET; QoS; Security; Security Service Vector